Critical utopian citizenship: theory and practice - Firth, Rhiannon (2010)
This project seeks to bring a critical utopian methodology to bear upon the institution of citizenship in the hope of imagining a theoretical formulation that could encourage active, anti-hierarchical, participatory and empowering practices. The critical utopian approach disrupts conventional disciplinary boundaries, and allows theories and practices that would not normally be associated with citizenship to be brought into dialogue with the concept in thought and imagination, as part of a strategic intervention. This produces a perspective that is simultaneously estranging and creative, deconstructive and experimental. The body of the work considers three themes in particular: territory, authority and rights, which are frequently posited as foundational for politics and citizenship, and proceeds to deconstruct their dominant formulations by imagining an infinitely critical utopian ‘outside’. Diverse bodies of theory including post-structuralism, anarchism, post-structural and post-left anarchisms, ecology, critical geography and feminism are drawn upon to articulate critical utopias of space without territory, decision-making without authority and ethics without rights. The project then brings another ‘outside’ into dialogue with the theory: practices in what are termed ‘autonomous utopian communities’; including intentional communities, autonomous social centres, housing co-operatives and eco-villages. The aim of the project is to use a dialogue between critically resistant theories and practices to expose the obscured normative and indeed utopian foundations of many dominant theories of citizenship, and to consider the ethical and practical effects of hegemonic and truth-claiming discourses. The project also posits something different: a contingent and open-ended critical utopian citizenship that favours perspectival multiplicity, process over closure, and contingency over certainty, that can be engaged in by citizens and non-citizens in everyday life.